2018
DOI: 10.1021/acs.jafc.7b06010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Geographical and Botanical Origin of Hops (Humulus lupulus L.) Using Stable Isotopes of C, N, and S

Abstract: A need exists for a reliable method to determine the geographical and botanical origin of hops. For this study, three sets of samples were collected: the first set comprised 5 German samples; the second set comprised samples of hops from 10 of the world's major hop-growing regions; and the third comprised the 4 main Slovenian regions. The samples were analyzed using isotope ratio mass spectrometry (IRMS) to obtain δC, δN, and δS values. The δN (2.2 ‰ to 8.4 ‰) and δS (0.7 ‰ to 12.3 ‰) values were the most disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…Promising methods, some of which are already being used routinely, relate to the detection of animal commodities, such as meat, dairy products, fish, and shellfish with regard to the detection of the geographical origin, the feeding method of the animals, the production method (organic vs conventional) or whether it is wildlife or breeding [155]. In addition, there are numerous examples of applications for plant-based foods, which mainly refer to the proof of geographical origin, the fertilizers used, and the botanical origin, for example for hops [156], ginseng [157], and tomatoes [158].…”
Section: Metallomics-and Isotoplomics-based Methodsmentioning
confidence: 99%
“…Promising methods, some of which are already being used routinely, relate to the detection of animal commodities, such as meat, dairy products, fish, and shellfish with regard to the detection of the geographical origin, the feeding method of the animals, the production method (organic vs conventional) or whether it is wildlife or breeding [155]. In addition, there are numerous examples of applications for plant-based foods, which mainly refer to the proof of geographical origin, the fertilizers used, and the botanical origin, for example for hops [156], ginseng [157], and tomatoes [158].…”
Section: Metallomics-and Isotoplomics-based Methodsmentioning
confidence: 99%
“…No statistically significant difference was observed in the δ 13 C values (average −26.7 ± 0.8‰) between conventionally and organically produced hops. However, δ 15 N values in European samples were lower than the organically produced hops [24].…”
Section: Hops and Beer Samplesmentioning
confidence: 67%
“…However, most literature studies are concerned with source identification, and it appears that there are no published studies on the type of production regime, i.e., conventional versus organic beer. For example, δ 13 C values were applied in studies to identify the geographical and botanical source of plants used for beer production [17,18,23,24], rather than management practice discrimination.…”
Section: Stable Isotopesmentioning
confidence: 99%
“…In particular, the clams from JN showed the lowest discrimination rate, where only 14 clams were appropriately identified and 12 clams were found to have other origins. Although previous studies have shown that the combination of δ 13 C and δ 15 N can be used for determining the geographical origins of agricultural products, plants, and meat [48,49], we have demonstrated the necessity of adding other factors that can increase the ability to identify habitats and other geographic information in food products, such as bivalves [19]. Given that the values of δD, δ 18 O, and δ 34 S measured in clams from the three regions of Korea did not demonstrate great discriminatory power against LDA [19], FAs were additionally selected in the next step of this study as a potential parameter for providing habitat information.…”
Section: First Step: a Dual-isotope Analysis For Distinct Geographica...mentioning
confidence: 99%